A STUDY ON PROGRESS OF MICRO FINANCE INSTITUTIONS BANK LINKAGE PROGRAM IN INDIA - Shaik, Haseena; Banana, Dr. Krishna (IJRDO - Journal of Business Management, 2018)
Micro Finance Institutions (MFIs) act as an important channel for extending financial services to the microfinance sector in the country by raising resources from Banks and other institutions and extending loans to individuals or members of SHGs/JLGs. MFIs have evolved into a vibrant segment of financial sector exhibiting a variety of business models in recent years. The Indian Microfinance Sector has witnessed a phenomenal growth over the past few years. The number of Institutions providing microfinance services has gone up from a few to several hundreds. The Government of India and the Reserve Bank of India has created conducive policy and regulatory framework for Microfinance Institutions (MFIs) to operate in the country. The quantum of credit made available to the poor and financially excluded clients has gone past Rs.60,000 crore and number of clients benefitted is close to 40 million as of March 2016. The present research article is to study the overall progress of MFI-Bank Linkage Program.